Natural Resource Capital for Sustainable Livelihoods in Social Forestry Areas: A Case Study from Enrekang Regency - Astaman, Putra; Hikmah, Aulia Nurul; Dassir, Muhammad; Nadirah, St (Tarjih : Agribusiness Development Journal, 2024)
The main problem is how natural resource management, especially forests, can improve community welfare without compromising environmental sustainability. This study aims to analyze the role of natural resource capital in supporting sustainable livelihoods in the social forest area of Enrekang Regency and evaluate the social and economic impacts of the social forestry program implemented in the area. The research method used is a qualitative approach with in-depth interviews with communities and relevant stakeholders and analysis of relevant secondary data. The research findings show that the social forestry program provides positive impacts through increased income, food security, and employment opportunities for the community. However, there are still challenges in the form of a lack of technical knowledge and dependence on illegal logging practices. This research makes a new contribution by exploring the potential for collaboration between the government, communities, and non-governmental organizations in sustainable social forest management. In conclusion, the success of social forest management is highly dependent on strengthening community capacity and implementing environmentally friendly forestry practices. The policy implication of this finding is the importance of government support in providing technical training and supervision of social forestry programs. The recommendation for future research is to conduct further studies on the long-term impact of the agroforestry program in improving economic and environmental sustainability in social forest areas.